2017
DOI: 10.17511/ijmrr.2017.i07.01
|View full text |Cite
|
Sign up to set email alerts
|

Post-Neonatal tetanus from broomstick injuries: a word of caution for caregivers

Abstract: Tetanus is a vaccine-preventable disease that is acquired through exposure to the spores of the bacterium Clostridium tetani which are ubiquitous in the soil. Post-neonatal tetanus is an increasing problem in developing countries, including Nigeria. This is mainly as a result of inadequate immunization coverage, unsustainable immunization programmes, and non-administration of booster doses of tetanus toxoid at appropriate periods to eligible children. The spores of the bacterium can get into the body through b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(29 reference statements)
2
1
0
Order By: Relevance
“…Lack of immunisation with primary and booster doses of TT or incomplete immunisation have been identified as major risk factors for the persistence of post neonatal tetanus in Nigeria [5,15,26,27,28]. In this study, as much as 79.2% of the children were either not immunised or were incompletely immunised with TT containing vaccines in infancy, which is consistent with the reports from other studies in Nigeria [8,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…Lack of immunisation with primary and booster doses of TT or incomplete immunisation have been identified as major risk factors for the persistence of post neonatal tetanus in Nigeria [5,15,26,27,28]. In this study, as much as 79.2% of the children were either not immunised or were incompletely immunised with TT containing vaccines in infancy, which is consistent with the reports from other studies in Nigeria [8,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…In earlier studies conducted in Port Harcourt, [8,30] broomstick injury was however the commonest portal of entry. This portal of entry for PNT was also documented by Komomo et al [31] and Ijiezie et al [36] in Calabar and Uyo respectively. The study at Uyo, reported that this injury is obtained when caregivers flog their children with the broom, mostly when upset with them.…”
Section: Discussionsupporting
confidence: 74%
“…The study at Uyo, reported that this injury is obtained when caregivers flog their children with the broom, mostly when upset with them. [36] It is however interesting to note that broomstick injury as a portal of entry was only documented in studies carried out in the south-south geopolitical region of Nigeria and not in other parts of the country [26][27][28][29][30] or in other countries. [33,35] One can only ponder at this stage if this behaviour of using broom to flog children is peculiar to this geopolitical zone of the country or if it was erroneously omitted in studies from other parts of Nigeria.…”
Section: Discussionmentioning
confidence: 99%